A chaos theory approach to understanding the impact of the COVID-19 pandemic on tourism businesses in Plateau State, Nigeria - Iirmdu, Tina Odinakachi (Stellenbosch : Stellenbosch University, 2022)
Thesis (DPhil)--Stellenbosch University, 2022.